An analysis of the onomatopoeia in “COCO” movie - Fira Sabrina; Winanda Aghniya Puteri (Mitra Palupi, 2022)
Background: when people watch movies, they not only enjoy the pictures and the action but also related to linguistic expression. One of them is onomatopoeia, which makes dialogue in the film becomes more interesting. Purpose: This research aims to describe kind of onomatopoeic words used in the COCO movie. Design and methods: This method of this research was a descriptive qualitative research. The data were analyzed for collecting the primary and secondary onomatopoeia. In collecting the data for the analysis the source data was taken from the movie entitled “COCO”. In collecting data, at this step, there were some steps that would be applied by the researchers: 1) Watch the movie, 2) Identify the dialogues and action which had Onomatopoeia from the movie, 3) List the Onomatopoeic words by marking and selecting the onomatopoeic words from the movie by applying note taking technique Results: this research revealed 20 onomatopoeic expressions or words and these 20 expressions were divided into 3 classifications, namely the first classification is onomatopoeic words, the second classification is onomatopoeic meaning, and the third classification is contextual meaning. Furthermore, this study exposed 9 primary onomatopoeia and 11 secondary onomatopoeia from the data. Based on the classification of onomatopoeia with the voice described, the researchers found 8 human voice data, 1 animal voice data, 11 other sounds.